2017
DOI: 10.3906/vet-1609-65
|View full text |Cite
|
Sign up to set email alerts
|

Pathological and immunohistochemical evaluation of skin and teat papillomas in cattle

Abstract: Bovine skin and teat papillomas were examined for immunohistochemical expression of bovine papillomavirus (BPV), proliferating antigens (PCNA, Ki-67), CD3 + T lymphocytes, and some of the type III intermediate filaments. Papillomas showed epidermal hyperplasia, koilocytes, and hyperkeratosis with prominent dermal connective tissue. Immunohistochemistry found the presence of BPV antigens in the nuclei of granulosa cells. PCNA and Ki-67 revealed positive nuclear staining in the dermis and epidermis. Perivascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 25 publications
(81 reference statements)
3
4
0
Order By: Relevance
“…There was also epidermal maculopapular evidence of an erosive epidermal lesion. These re-sults concurred with those reported elsewhere [17]. The affected keratinocytes had larger nuclei, eosinophilic intracytoplasmic inclusion bodies, and vacuolation.…”
Section: Discussionsupporting
confidence: 92%
“…There was also epidermal maculopapular evidence of an erosive epidermal lesion. These re-sults concurred with those reported elsewhere [17]. The affected keratinocytes had larger nuclei, eosinophilic intracytoplasmic inclusion bodies, and vacuolation.…”
Section: Discussionsupporting
confidence: 92%
“…However, despite the wide variety of BPVs identified in this study, the same papilloma-associated histological changes were observed in all the samples, and there was no correlation between the gross pattern and the BPV type identified. Although not considered pathognomonic of BPV infection, the presence of koilocytes observed in the histological analysis likely indicates the cytopathic effect of the papillomavirus in the tissues [2,5]. PCR assays using the FAP59/FAP64 degenerate primers to amplify partial fragments of the BPV L1 gene, followed by sequencing of the amplified product, is an important tool that is widely used to determine the presence of different BPV types in cattle herds from different geographical regions [1,10,18,21,23,25].…”
Section: Discussionmentioning
confidence: 99%
“…Papillomas may be large enough to interfere with the milking process and milk flow, especially when they are located near the sphincter of the teat, predisposing the cattle to mastitis. In addition, ulceration and rupture of the lesions may result in bleeding and distortion of the lactiferous ducts [5,6,8,15,19,25].…”
Section: Introductionmentioning
confidence: 99%
“…In Beytut (2017), on the other hand, observed widespread epidermal hyperplasia, acanthosis and hyperkeratosis, as well as an increase in connective tissue in the dermis. However, koilocytes have seen balloon-like degeneration, pycnotic and nuclear fragmentation containing dense chromatin.…”
Section: Discussionmentioning
confidence: 97%